Effects of walking speed on knee joint loading estimated via musculoskeletal modeling - Haight, Derek Joseph, author; Browning, Ray, advisor; Reiser, Raoul, committee member; Puttlitz, Christian, committee member; Greene, David, committee member (Colorado State University. Libraries, 2012)
Walking is the most common form of physical activity and is assumed to incur a relatively small risk of musculoskeletal injury. However, walking related- musculoskeletal injuries, particularly at the knee joint, are not uncommon in individuals who walk for exercise. Surprisingly, there is scant data regarding how walking conditions (e.g. speed, grade, surface) affect loads (i.e. contact forces) across lower extremity joints. Studies to date have used proxy measures of joint loading, primarily net muscle moments (NMM); however the validity of these proxy measures to estimate joint contact forces (JCF) is not well established. The purpose of this study was to estimate knee JCFs during slow, moderate and fast walking and to examine the validity of NMMs to estimate JCFs. We hypothesized that both knee JCFs and sagittal plane NMMs would increase with walking speed, but that the increases in NMMs would be much greater than the increases in axial JCFs. We collected kinematic and kinetic data as ten adults (mass = 67.2 (12.0) kg, mean (SD)) walked on a dual-belt force measuring treadmill at 0.75, 1.25, and 1.50 m•s-1. An OpenSim three-dimensional musculoskeletal model with 23 degrees of freedom and 92 muscle actuators was scaled to each subject. We calculated NMMs and muscle forces via inverse dynamics and static optimization, respectively, for 5 gait cycles per subject at each speed. We determined knee JCFs from the vector sum of the joint reaction force and individual muscle forces crossing the knee joint, in the tibial reference frame. During weight acceptance in early stance, axial and anterior-posterior knee JCFs increased by ~30% and 175%, respectively as walking speed increased from 0.75 m•s-1 to 1.50 m•s-1. At the same point in the gait cycle, peak sagittal plane extensor NMM increased by over 200% (P<0.001) as speed increased. The modest differences in axial knee JCFs with walking speed, suggest that slower speeds may not reduce joint loading substantially. Additionally, our results suggest that NMMs are not a good proxy measure of axial JCFs and that detailed musculoskeletal models should be used to quantify the effects of walking conditions on joint loading.
Keywords: OpenSim; net muscle moments; tibiofemoral; contact forces; gait